The Effect of Using Blended Learning Strategy Toward The Students’ Vocabulary Mastery at Tenth Grade of SMKN 2 Sungai Penuh - Tri Saswandi; Pretty Elisa Ayu Ningsih (Jurnal Ilmiah Wahana Pendidikan, 2023)
Based on preliminary observations conducted at SMKN 2 Sungai Penuh, researchers found some students could not understand English well because of lack of vocabularies. As a result, they did not involve actively in learning process, they just kept silent when their teacher asked them questions. This research was aimed to find whether there was any significant effect of using Blended Learning strategy in teaching vocabulary at the eighth grade Students of SMKN 2 Sungai Penuh Academic year 2021/2022. The researchers used quantitative method with quasy experimental model. The population in this research was all students at tenth grade of SMK Negeri 2 Sungai Penuh (198 students). Samples in this research was class X TKR control class that taught by using lecturing strategy and class X TSM as experiment class was taught by using Blended Learning Strategy. The sample is determined by using random sampling technique. The instrument in this research was test, the test used in this research was vocabulary test. The simple regression model in this research was analyzed by using SPSS program (Statistical Product and Service Solution) 2600 for window and Ms. Excel 2010. The data was analyzed by using regression linier, the formula was T-test. Based on the result, it can be concluded that hypothesis H0 was rejected and H1 was accepted. It meant that there was significant effect of Using Blended Learning Strategy in Teaching Vocabulary at the Tenth grade Students’ of SMKN 2 Sungai Penuh Academic Year 2021/2022. It can be concluded that Blended Learning strategy was better than lecturing model in teaching English vocabulary at Tenth grade students’ of SMKN 2 Sungai Penuh Academic Year 2021/2022. In other words Blended Learning strategy gave a good effect on students’ understanding in English vocabulary.